Diammonium Glycyrrhizinate Ameliorates Obesity Through Modulation of Gut Microbiota-Conjugated BAs-FXR Signaling - Li, Yun; Hou, Huiqin; Wang, Xianglu; Dai, Xin; Zhang, Wanru; Tang, Qiang; Dong, Yue; Yan, Chen; Wang, Bangmao; Li, Zhengxiang; Cao, Hailong (Frontiers in Pharmacology, 2021)
Obesity is a worldwide epidemic metabolic disease. Gut microbiota dysbiosis and bile acids (BAs) metabolism disorder are closely related to obesity. Farnesoid X-activated receptor (FXR), served as a link between gut microbiota and BAs, is involved in maintaining metabolic homeostasis and regulating glucose and lipid metabolism. We previously reported that diammonium glycyrrhizinate (DG) could alter gut microbiota and prevent non-alcoholic fatty liver disease. However, it remains ambiguous how DG affects the gut microbiota to regulate host metabolism. In this present study, 16S rRNA Illumina NovaSeq and metabolomic analysis revealed that DG treatment suppressed microbes associated with bile-salt hydrolase (BSH) activity, which, in turn, increased the levels of taurine-conjugated BAs accompanied by inhibition of ileal FXR-FGF15 signaling. As a result, several obesity-related metabolism were improved, like lower serum glucose and insulin levels, increased insulin sensitivity, few hepatic steatosis and resistance to weight gain. Additionally, decreased level of serum lipopolysaccharide (LPS) was observed, which contributed to a strengthened intestinal barrier. The effect of DG on weight loss was slightly enhanced in the antibiotics-treated obese mice. Collectively, the efficacy of DG in the treatment of obesity might depend on gut microbiota-conjugated BAs-FXR axis. Hence, it will provide a potential novel approach for the treatment of obesity.